2017
DOI: 10.1021/acsami.7b12615
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Flux and Electrochemical Cleaning of Silicate Scaling on Carbon Nanotube-Coated Membrane Distillation Membranes Treating Geothermal Brines

Abstract: The desalination of inland brackish groundwater offers the opportunity to provide potable drinking water to residents and industrial cooling water to industries located in arid regions. Geothermal brines are used to generate electricity, but often contain high concentrations of dissolved salt. Here, we demonstrate how the residual heat left in spent geothermal brines can be used to drive a membrane distillation (MD) process and recover desalinated water. Porous polypropylene membranes were coated with a carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 68 publications
(143 reference statements)
2
55
0
Order By: Relevance
“…However, commercial hydrophobic PTFE membranes with a hydrophilic polyurethane (PU) surface layer were used successfully in DCMD on real poultry, fish, and bovine stick waters [17]; a metal microfiltration membrane was used to capture fats prior to DCMD. Tang et al [18] showed how hydroxide ion generation, driven by water electrolysis on the electrically conducting membrane surface consisting of carbon nanotubes and a polyvinyl alcohol layer over a hydrophobic layer, can be used to efficiently dissolve silicate scaling that developed during the process of desalinating the geothermal brine by MD, negating the need for chemical cleaning. Note: a previous study employing coated HFMs with porous polyfluorosiloxane coatings operated with crossflow mode of hot produced water containing silica did not show any fouling [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, commercial hydrophobic PTFE membranes with a hydrophilic polyurethane (PU) surface layer were used successfully in DCMD on real poultry, fish, and bovine stick waters [17]; a metal microfiltration membrane was used to capture fats prior to DCMD. Tang et al [18] showed how hydroxide ion generation, driven by water electrolysis on the electrically conducting membrane surface consisting of carbon nanotubes and a polyvinyl alcohol layer over a hydrophobic layer, can be used to efficiently dissolve silicate scaling that developed during the process of desalinating the geothermal brine by MD, negating the need for chemical cleaning. Note: a previous study employing coated HFMs with porous polyfluorosiloxane coatings operated with crossflow mode of hot produced water containing silica did not show any fouling [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the presence of electrical potential conductive filters can instantly remove, kill or inactivate microorganisms by various mechanisms such as direct and indirect oxidation, Coulombic repulsion, bubble generation, Joule heating, and local pH change. [46][47][48][49][50][51][52][53] The electrical conductivity of the conductive filters might also contribute to lipid membrane disruption through the electroporation process. 14,[54][55][56] Thus the physicochemical and electrochemical manifold effects of graphene, including LIG filters, can potentially also be useful for inactivation of viruses.…”
Section: Many Researchers Have Explored the Various Mechanisms By Which Graphene-based Filters Canmentioning
confidence: 99%
“…(Supplementary Material). As the feed becomes more concentrated, due to continuing water recovery, membrane fouling becomes more pronounced; this is caused by accelerated deposition of foulants, such as organic molecules and particulate matter onto the membrane surface, which blocks the flow of water (Tang et al, 2017). Membrane autopsies of the fouled membranes were performed using SEM (a qualitative measure) and XPS (a quantitative measure).…”
Section: Membrane Distilation Performancementioning
confidence: 99%